Molecular Characterization of Peroxisome Proliferator-Activated Receptor-Gamma Coactivator-1α (PGC1α) and Its Role in Mitochondrial Biogenesis in Blunt Snout Bream (Megalobrama amblycephala) - Song, Xiaojun; Rahimnejad, Samad; Zhou, Wenhao; Cai, Linsen; Lu, Kangle (Frontiers in Physiology, 2019)
PGC1α is a transcriptional coactivator that plays key roles in mitochondrial biogenesis, so exploring its molecular characterization contributes to the understanding of mitochondrial function in cultured fish. In the present study, a full-length cDNA coding PGC1α was cloned from liver of blunt snout bream (Megalobrama amblycephala) which covered 3741 bp with an open reading frame of 2646 bp encoding 881 amino acids. Sequence alignment and phylogenetic analysis revealed high conservation with other fish species and other higher vertebrates. Based on the PGC1α amino acid sequence, Thr177 has mutated to proline residue in blunt snout bream. To investigate PGC1α function, three in vitro tests were carried out using primary hepatocytes of blunt snout bream. In order to explore the effect of AMPK activity on expression of PGC1α gene, hepatocytes were cultured with activator/inhibitor (metformin/compound C) of AMPK, and then PGC1αexpression was analyzed. The results showed no significant alteration in PGC1α expression by AMPK activation/inhibition. Small interfering RNA (si-RNA) technology was implemented to knock-down PGC1α expression to further explore the process of mitochondrial biogenesis. No significant differences in expression level of NRF1 and TFAM and mtDNA copy number were found between control and si-RNA groups. Also, hepatocytes were cultured with oleic acid, and the findings showed the significant reduction of mtDNA copy number in oleic acid group compared to control. Moreover, oleic acid down-regulated the expression of NRF1 and TFAM genes, while PGC1α expression level remained unchanged. In summary, as a critical phosphorylation site of PGC1α (Thr177) which is targeted by AMPK has mutated; activation/inhibition of AMPK had no effects on PGC1α expression. Moreover, the findings in this study indicated that PGC1α did not correlate with mitochondrial biogenesis in hepatocytes of blunt snout bream as it had no effects on the expression of NRF1 and TFAM genes.